Outcomes in patients with heart failure treated in hospitals with varying admission rates: population-based cohort study. Issue 12 (30th July 2014) - Bhatia, R Sacha; Austin, Peter C; Stukel, Therese A; Schull, Michael J; Chong, Alice; Tu, Jack V; Lee, Douglas S
Abstract : Study objectives: Hospital admission rates for patients with heart failure (HF) presenting for emergency department (ED) care vary, and the implications of direct discharge home from the ED are unknown. We examined whether patients treated in hospitals with low admission rates exhibit higher rates of repeat ED visits, hospital readmissions and death. Methods: We divided EDs into low-, medium- and high-admission-rate tertiles by their standardised HF admission rate in Ontario, Canada. Among adults (≥18 years) with HF discharged from an ED between April 2004 and March 2010, we evaluated the primary outcomes of repeat ED visits or hospitalisations for HF, and secondary outcomes, which included death, within 30 days stratified by HF admission-rate tertile. Results: 89 878 patients with HF presented to low- (n=29 929), medium- (n=30 900) or high- (n=29 049) admission-rate institutions, with hospitalisation rates of <67%, 67–75% and >75%, respectively. Among 28 175 ED-discharged patients, the multivariable-adjusted HR for repeat ED visit or hospitalisation for HF at low-admission-rate institutions was 1.18 (95% CI 1.07 to 1.29, p<0.001) compared with high-admission institutions. Similarly, the HR for repeat ED visits for HF was 1.28 (95% CI 1.14 to 1.44, p<0.001) at low-admission hospitals. Compared with discharged patients in the high-admission-rate tertile, adjusted HR for 30-day mortality was 1.19 (95% CI 0.95 to 1.47) at low-admission-rate hospitals. The HRs for all of the above outcomes were not significantly increased at medium-admission-rate hospitals. Discussion: Patients seeking care at institutions with lower rates of HF admission showed higher rates of repeat ED visits or hospitalisations after previous ED discharge.